1989
DOI: 10.1200/jco.1989.7.9.1310
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study with the combination etoposide, doxorubicin, and cisplatin in advanced measurable gastric cancer.

Abstract: In this phase II multicenter trial, 67 evaluable patients with advanced measurable gastric carcinoma were treated with a combination of etoposide, Adriamycin (doxorubicin; Adria Laboratories, Columbus, OH), and cisplatin (EAP). The overall response rate was 64%, including 21% complete responses (CRs). In 55 patients with metastatic disease, 31 responses (51%) including eight CRs (15%) were achieved. Responses were seen in all metastatic sites, but the response rate was lower in patients with peritoneal carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
121
2
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(127 citation statements)
references
References 26 publications
2
121
2
2
Order By: Relevance
“…In phase II trials, response rates up to 60% have been reported for regimens such as FAMTX, ELF, EAP, Cisplatin/5-FU or ECF (Klein et al, 1986;Preusser et al, 1989;Wilke et al, 1990;Findley and Cunningham, 1993;Wils, 1996). However, in randomised phase III trials, this high level of activity has only been confirmed for the ECF-regimen (Webb et al, 1997;Waters et al, 1999), whereas for the FAMTX, ELF or cisplatin/5-FU-regimen response rates of 20-25% have been reported (Kelsen et al, 1992;Wilke et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In phase II trials, response rates up to 60% have been reported for regimens such as FAMTX, ELF, EAP, Cisplatin/5-FU or ECF (Klein et al, 1986;Preusser et al, 1989;Wilke et al, 1990;Findley and Cunningham, 1993;Wils, 1996). However, in randomised phase III trials, this high level of activity has only been confirmed for the ECF-regimen (Webb et al, 1997;Waters et al, 1999), whereas for the FAMTX, ELF or cisplatin/5-FU-regimen response rates of 20-25% have been reported (Kelsen et al, 1992;Wilke et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] However, none of the combination regimens have yet demonstrated a prolongation of survival as compared with 5-fluorouracil alone; [6][7][8] accordingly new active chemotherapy regimens are needed. Irinotecan hydrochloride (CPT-11) is a water-soluble, semisynthetic derivative of camptothecin (CPT) that retains the original antitumor activity of CPT, but has lower toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of 5-fl uorouracil (5-FU), doxorubicin, and mitomycin-C (FAM) was considered the standard regimen until the FAMTX schedule (including 5-FU, doxorubicin, high-dose methotrexate, and leucovorin) was shown to be superior in terms of both response rates (41% vs 9%) and overall survival (42 vs 29 weeks) [8]. On the other hand, cisplatin (CDDP)-based regimens demonstrated response rates of between 37% and 72% in phase II studies [9,10], although these results were not confi rmed in phase III studies [11][12][13]. More recently, the ECF combination regimen of CDDP, epirubicin (EPI), and infusional 5-FU proved very effective in phase II studies [14,15], and it was superior to FAMTX in terms of response rates (46% vs 21%; P = 0.0002) and overall survival (8.7 vs 6.1 months; P = 0.0005) in a randomized phase III comparison, with mild toxicity (16).…”
Section: Introductionmentioning
confidence: 99%